2021
DOI: 10.1021/acs.langmuir.1c00700
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional MOF Modulated Fiber Nanogenerator for Effective Acoustoelectric Conversion and Human Motion Detection

Abstract: The real-time application of piezoelectric nanogenerators (PNGs) under a harsh environment remains a challenge due to lower output performance and poor durability. Thus, the development of flexible, sensitive, and stable PNGs became a topic of interest to capture different human motions including gesture monitoring to speech recognition. Herein, a scalable approach is adapted where naphthylamine bridging a [Cd­(II)-μ-I4] two-dimensional (2D) metal–organic framework (MOF)-reinforced poly­(vinylidene fluoride) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 56 publications
(124 reference statements)
0
47
0
Order By: Relevance
“…To explore the versatile applications of the PNG for human physiological motion sensing, the PNG was conformally affixed to various parts of the body to provide body-wide physiological signal and joint movement monitoring. ,, While PNG is attached to the human skin, the subtle deformation of the PNG generates an electrical signal due to movement of the human body. The various regions of the human body movement are illustrated in Figure a to accomplish health-care monitoring .…”
Section: Resultsmentioning
confidence: 99%
“…To explore the versatile applications of the PNG for human physiological motion sensing, the PNG was conformally affixed to various parts of the body to provide body-wide physiological signal and joint movement monitoring. ,, While PNG is attached to the human skin, the subtle deformation of the PNG generates an electrical signal due to movement of the human body. The various regions of the human body movement are illustrated in Figure a to accomplish health-care monitoring .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Zr-based MOF can also be used for SO 2 detection, and the results show that it has high sensitivity and excellent flexibility [ 125 ]. Roy et al [ 126 ] incorporated 2D MOF into PVDF, and the structure of MOF is shown in Figure 7 (1). The composite fiber-based piezoelectric nanogenerator (C-PNG) was prepared by the electrospinning method.…”
Section: Preparation Of Pvdf Nfs By Electrospinningmentioning
confidence: 99%
“…Reprinted with permission from Ref. [ 126 ], copyright 2021, American Chemical Society. ( 2 ) Analysis of piezoelectric properties during human movement, ( a ) voltage responses of C−PNGs attached to a wrist, ( b ) elbow, ( c ) neck, ( d ) knee, ( e ) toe, and ( f ) heel movements, the arrows represent pressure and release.…”
Section: Figurementioning
confidence: 99%
“…The flexible and transparent 4 mm 2 ACEL display arrays successfully exhibited pattern Z (Figure 14e). In 2021, a 2D metal-organic framework (MOF) and polyvinylidene fluoride (PVDF)based piezoelectric nanogenerators were presented by Sinha and Mandal et al [79]. In addition to the excellent piezoelectric output at as high a power density as 24 µW•cm −2 , an acoustoelectric application was demonstrated (Figure 15a).…”
Section: Self-powered Sensor Integrationmentioning
confidence: 99%